Taxanes in the Treatment of Head and Neck Squamous Cell Carcinoma - Ching-Yun Hsieh; Ching-Chan Lin; Wei-Chao Chang (Biomedicines, 2023)
Taxanes, particularly docetaxel (DTX), has been widely used for combination therapy of head and neck squamous cell carcinoma (HNSCC). For locally advanced unresectable HNSCC, DTX combined with cisplatin and 5-fluorouracil as a revolutionary treatment revealed an advantage in the improvement of patient outcome. In addition, DTX plus immune check inhibitors (ICIs) showed low toxicity and an increased response of patients with recurrent or metastatic HNSCC (R/M HNSCC). Accumulated data indicate that taxanes not only function as antimitotics but also impair diverse oncogenic signalings, including angiogenesis, inflammatory response, ROS production, and apoptosis induction. However, despite an initial response, the development of resistance remains a major obstacle to treatment response. Taxane resistance could result from intrinsic mechanisms, such as enhanced DNA/RNA damage repair, increased drug efflux, and apoptosis inhibition, and extrinsic effects, such as angiogenesis and interactions between tumor cells and immune cells. This review provides an overview of taxanes therapy applied in different stages of HNSCC and describe the mechanisms of taxane resistance in HNSCC. Through a detailed understanding, the mechanisms of resistance may help in developing the potential therapeutic methods and the effective combination strategies to overcome drug resistance.